Closed testing procedure for multiplicity control. An application on oxidative stress parameters in Hashimoto's Thyroiditis - Angela Alibrandi (Epidemiology, Biostatistics and Public Health)
Closed Testing procedures represent an effective solution to the need to make inferences on multiple aspects at the same time, controlling the Familywise Error Rate (FWER), that is the error rate of the hierarchical family. Closed Testing procedures have a high degree of adaptability to a wide range of experimental situations, both in parametric than in non-parametric ambit. The attention is focused on the  Bonferroni-Holm method, frequently used to counteract the problem of multiple comparisons. The present paper aims to show an original application of the Closed Testing procedures for multiplicity control in medical research, with reference to the oxidative stress; in particular the Min-P Bonferrroni-Holm method was applied to the p-value adjustment, related to three parameters (BAP, D-ROMS, AGEs) of oxidative stress in Hashimoto’s thyroidytis.